PEMAHAMAN MATERI TERHADAP HASIL BELAJAR MAHASISWA PADA MATAKULIAH PRAKTEK - Mellasanti Ayuwardani (CV. ALIM'SPUBLISHING, 2023)
Practical lectures in their implementation require an understanding of how to carry out these activities. Not just knowledge, but understanding is needed. Lack of understanding can lead to inappropriate practicum results. The problem of this research is